Reality television the TV phenomenon that changed the world - Deller, Ruth A.; Emerald Publishing Limited (Bingley Emerald Publishing Limited, 2020)
Reality television is one of the defining genres of the 21st century. It is shown worldwide, features people from all walks of life and covers everything from romance to religion. It has not only changed television, but every other area of the media.
So why has reality TV become such a huge phenomenon, and what is its future in an age of streaming and social media?
This book provides an overview of key theories and debates in the study of reality television and discusses industry practices in their global and national contexts. Deller also explores, through interviews with participants and analyses of key programmes, why people take part in reality TV, how they are represented and impact this has on their lives.
From its documentary roots to its social media present and future - this is a guide to Reality Television: The TV Phenomenon that Changed the World.
Includes index (pages 201-208).
Keywords: Great Britain .; Reality television programs .; Reality television programs -- Great Britain